Hot, Humid Air Decontamination of Aircraft Confirmed That High Temperature and High Humidity Are Critical for Inactivation of Infectious, Enveloped Ribonucleic Acid (RNA) Virus - Buhr, Tony L.; Young, Alice A.; Borgers-Klonkowski, Erica; Kennihan, Neil L.; Barnette, Harold K.; Minter, Zachary A.; Bohmke, Matthew D.; Osborn, Emily B.; Hamilton, Shelia M.; Kimani, Monique B.; Hammon, Mark W.; Miller, Charles T.; et al. (Frontiers in Bioengineering and Biotechnology, 2020)
Aims: To develop infectious (live/dead) enveloped virus test indicators and Response Surface Methodology (RSM) models that evaluate survival of an enveloped ribonucleic acid (RNA) virus on contaminated aircraft materials after exposure to hot, humid air (HHA). Methods and Results: Enveloped RNA bacteriophage Phi6 (ϕ6) was dried on wiring insulation, aircraft performance coating (APC), polypropylene, and nylon at ≥8 log10 plaque-forming units (PFU) test coupon-1. Only 2.4 log10 inactivation was measured on APC at 70°Celsius (°C), 5% relative humidity (RH) after 24 h. In contrast, HHA RSM models showed a 90% probability of a 7-log10 inactivation at ≥63°C, 90% RH after 1 h, and decontamination kinetics were similar across different materials. HHA decontamination of C-130 and C-17 aircraft showed >7 log10 and ≥5.9 log10 inactivation of enveloped virus on 100 and 110 test indicators, respectively, with a 1-h treatment, excluding ramp-up and ramp-down times. Conclusions: Enveloped RNA virus test indicators were successfully developed, lab tested for HHA decontamination, analyzed for RSM, and field-tested in aircraft demonstrations. Significance and Impact of the Study: The utility of HHA decontamination was demonstrated after inactivating enveloped RNA virus on aircraft with a 1-h HHA treatment within aircraft temperature and RH limits.